2018
DOI: 10.1108/mbe-06-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Operational performance measures for startups

Abstract: PurposeThe purpose of this study is to investigate the uses of performance measures in startup firms, including perceived importance and performance of those measures. Design/methodology/approachThe survey method is used in this study. Data are collected from founders/chief executive officers/managers of 110 startups in Thailand. The correlation analysis and analysis of variance techniques are used as the analysis tool in this study. FindingsThe results show that there is a positive relationship between the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 39 publications
0
29
0
5
Order By: Relevance
“…Measurements in Software Start-ups Some empirical studies have been done on measurement in start-ups, especially in operational performance measurement. For example, Rompho [23] in their study on performance measurements in start-ups highlight that "there is a positive relationship between the perceived importance and the performance of each metric". However, they found not no significant relationship between importance and performance of each metric among the various stages of start-ups.…”
Section: Related Workmentioning
confidence: 99%
“…Measurements in Software Start-ups Some empirical studies have been done on measurement in start-ups, especially in operational performance measurement. For example, Rompho [23] in their study on performance measurements in start-ups highlight that "there is a positive relationship between the perceived importance and the performance of each metric". However, they found not no significant relationship between importance and performance of each metric among the various stages of start-ups.…”
Section: Related Workmentioning
confidence: 99%
“…According to Petrů, Kramoliš, and Stuchlík (2020), in today's hyper-competitive times, companies are forced to develop their strategic approaches, especially towards customers. Various metrics play an important role in providing data for assessing economic efficiency (Rompho, 2018). In this context, controlling based on valid financial indicators (Gavel, 2016;Moeuf et al, 2017) plays an irreplaceable role.…”
Section: Discussionmentioning
confidence: 99%
“…According to the QUOTE research, which reviews the literature related to the definition of performance measurement systems for organizations, it is concluded that the interpretation of the performance system of organizations is divided into three categories, namely, the nature of the organization's performance measurement system, the role of the organization's performance measurement system and the process that is part of the organization's performance measurement system. Rompho (2018), after studying the financial success of organizations, divided financial success into two types, specifically, organizational operational success as determined by measuring the profits of the organization that are created using the existing resources of the current organization and applying the marketing sense that focuses on the value of the organization from the perspective of the investor. This value is based on the organization's financial performance indicators.…”
Section: Firm Performancementioning
confidence: 99%